Insights into the gut-liver axis: mechanisms and emerging therapies in hepatocellular carcinoma - Hu, Yongjian; Gao, Mingming; Chenghuang, Jiajin; Bao, Rui (Frontiers in Pharmacology, 2025)
The gut-liver axis is a multifaceted system where chemical and biological interactions between gut microbiota-derived metabolites and the liver significantly influence the development and progression of hepatocellular carcinoma Metabolites such as lipopolysaccharide (LPS), bile acids (BAs), and short-chain fatty acids (SCFAs) act as chemical mediators that modulate the tumor microenvironment through immune cell interactions and stromal activation, influencing tumor growth and metastasis. Changes in gut microbiota composition alter these signaling pathways, providing opportunities for therapeutic interventions. Strategies such as prebiotics, probiotics, and natural product-based small molecules have shown promise in modulating the gut-liver axis. Advanced multi-omics, chemical and bioinformatics tools, coupled with in vitro models like organoids, have unveiled intricate molecular interactions, offering insights into novel therapeutic targets. Future research should focus on delineating the pharmacological and immunological mechanisms within the gut-liver axis, developing personalized therapeutic strategies, and translating these findings into clinical applications.